REVITALISASI KECERDASAN MAJEMUK MELALUI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BAGI GENERASI Z - Bahiroh, Jihan Nur; Suradji, Muchamad; Sun’iyah, Siti Lathifatus (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2025)
The aim of writing this article is to provide ideas that are able to understand and apply them in learning Islamic Religious Education for generation Z with a multiple intelligence approach by Howard Gardner. There are nine multiple intelligences, namely linguistic intelligence, musical intelligence, logical-mathematical intelligence, spatial intelligence, bodily intelligence, social intelligence, personal intelligence, natural intelligence, and existential intelligence. The method used in the study is a descriptive qualitative research method involving primary data in the form of questionnaires for Generation Z (2011-2012) and interviews with Islamic Religious Education teachers at SMPN 1 Deket. The results show that natural, spatial, interpersonal, and intrapersonal intelligence are the dominant types of intelligence in Generation Z (2011-2012) and it can be concluded that the revitalization of multiple intelligences in Islamic Religious Education is not only relevant to the needs of 21st century learning, but also becomes a strategic approach in forming character and morals in the younger generation holistically.